Deterioration of phagocytosis in induced pluripotent stem cell-derived retinal pigment epithelial cells established from patients with retinitis pigmentosa carrying Mer tyrosine kinase mutations. (April 2021) - Tagawa, Miho; Ikeda, Hanako Ohashi; Inoue, Yumi; Iwai, Sachiko; Iida, Yuto; Hata, Masayuki; Asaka, Isao; Tsujikawa, Akitaka
Abstract: Retinitis pigmentosa (RP) is an incurable retinal degenerative disease with an unknown mechanism of disease progression. Mer tyrosine kinase ( MERTK ), which encodes a receptor of the Tyro3/Axl/Mer family of tyrosine kinases, is one of the causal genes of RP. MERTK is reportedly expressed in the retinal pigment epithelium (RPE) and is essential for phagocytosis of the photoreceptor outer segment. Here, we established induced pluripotent stem cells (iPSC) from patients with RP having homozygous or compound heterozygous mutations in MERTK, and from healthy subjects; the RP patient- and healthy control-derived iPSCs were differentiated into RPE cells. Although cytoskeleton staining suggested that polarity may have been disturbed mildly, there were no apparent morphological differences between the diseased and normal RPE cells. The internalization of photoreceptor outer segments in diseased iPSC-RPE cells was significantly lower than that in normal iPSC-RPE cells. This in vitro disease model may be useful for elucidating the mechanisms of disease progression and screening treatments for the disease. Highlights: ● RPE was successfully developed from iPSCs of RP patients with MERTK mutations. ● Phagocytosis of photoreceptor outer segments deteriorated in iPSC-RPE cells. ● The in vitro disease model of retinal degeneration can be useful for drug discovery.